Improving the use of perennial ryegrass swards for dairying in Ireland : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Agricultural Science at Massey University, Palmerston North, New Zealand - Tuñon, Gonzalo Enrique (Massey University, 2013)
The main objectives of this thesis were to investigate the effects of grazing severity, treading damage, re-growth interval and pre-grazing herbage mass (HM) on sward and animal performance in four experiments during 2009 and 2010 in Ireland. Experiment 1 investigated three post-grazing sward heights ranging from 3.6 to 4.9 cm during the main grazing season. Herbage accumulated and harvested (11.3 and 11.2 t dry matter (DM)/hectare (ha), respectively) were not significantly affected by grazing severity but there were sward morphological and structural differences. Experiment 2 quantified the effects of treading damage during two seasons, ranging from light to severe damage (3.3 to 13.3-cm hoof-print depths, respectively). Treading damage in a perennial ryegrass (PRG) sward on a well-drained soil did not reduce annual grass DM production. Treading in a creeping bent-dominated sward on a poorly-drained soil resulted in 14 to 51% reductions in cumulative yields depending on frequency and season. Experiment 3 examined the effects of 2-, 3- or 4-week re-growth intervals on herbage production, characteristics and tissue turnover of a PRG sward using marked tillers (n = 240) under a cutting regime. Cumulative HMs were 6.7, 9.1 and 10.4 t DM/ha for the 2-, 3- and 4-week re-growth treatments, respectively. The number of leaves appearing per tiller during the re-growth period was only optimum for the 4-week treatment. Experiment 4 also used marked tillers (n = 360) in a grazing dairy cow experiment during the main grazing season under three target pre-grazing HMs (945, 1,623 and 2,360 kg DM/ha >4 cm). The number of leaves appearing per tiller during the re-growth period was 1.0, 1.9 and 2.4 for low (L), medium (M) or high (H) pre-grazing HM treatments, respectively. Cows grazing L, M or H pre-grazing HM produced 343, 342 and 330 kg milksolids, respectively. Low pre-grazing-HM cows grazed for 90 min/day more than M and H pre-grazing-HM cows but there was no difference in individual intake (16.0 and 15.8 kg DM/cow/day in June and August, respectively). Post-grazing sward height, treading damage, re-growth interval and pregrazing HM can have a significant impact on the sward and on animal performance. The imposition of best management practice leads to a more effective conversion of grass into milk.
Ch. 7. published as: Tuñon, G., Lopez-Villalobos, N., Kemp, P.D., Kennedy, E, Hennessy, D., & O'Donavan, M. (2011). Effect of pre-grazing herbage mass on grazing behaviour, grass dry matter intake and milk production of dairy cows. Proceedings of the New Zealand Society of Animal Production, 71, 28-32.
Keywords: Ryegrasses; Pastures; Dairy cattle; Feeding and feeds; Ireland